2015
DOI: 10.1038/srep10357
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a distinct population of CD133+CXCR4+ cancer stem cells in ovarian cancer

Abstract: CD133 and CXCR4 were evaluated in the NCI-60 cell lines to identify cancer stem cell rich populations. Screening revealed that, ovarian OVCAR-3, -4 and -5 and colon cancer HT-29, HCT-116 and SW620 over expressed both proteins. We aimed to isolate cells with stem cell features sorting the cells expressing CXCR4+CD133+ within ovarian cancer cell lines. The sorted population CD133+CXCR4+ demonstrated the highest efficiency in sphere formation in OVCAR-3, OVCAR-4 and OVCAR-5 cells. Moreover OCT4, SOX2, KLF4 and NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 42 publications
4
77
0
2
Order By: Relevance
“…It is well described that low O 2 tension develops in tumors in vivo [64, 65] and promotes a CSC phenotype [66]. Our study revealed that selected pRCC cell lines exposed to hypoxia in vitro increased the expression of stem-related TFs ( oct-4 and sox2 ).…”
Section: Discussionsupporting
confidence: 61%
“…It is well described that low O 2 tension develops in tumors in vivo [64, 65] and promotes a CSC phenotype [66]. Our study revealed that selected pRCC cell lines exposed to hypoxia in vitro increased the expression of stem-related TFs ( oct-4 and sox2 ).…”
Section: Discussionsupporting
confidence: 61%
“…CD133 is a transmembrane glycoprotein with a unique structure of five transmembrane domains and two large extracellular glycosylation chains, expressed in both hematopoietic and neural stem cells (58). In several studies of HCC, the HSC surface marker CD133 was used to isolate LCSCs (47,54).…”
Section: Lcsc Surface Markers and Targeted Therapiesmentioning
confidence: 99%
“…The expression of CD133 and CXCR4 on CSCs has been evaluated in ovarian cancer cell lines [39]. Several ovarian cancer cell lines, such as OVCAR-3, -4, and -5 and colon cancer cells, SW620 and HCT-116 express both markers.…”
Section: Heterogeneity Of Tumor Cells Before Treatmentmentioning
confidence: 99%
“…Crosstalk between intracellular signaling pathways 7 Chronopharmacology + OVCAR-5 cells, and these cells were determined to be resistant to cisplatin in transplanted nude mice. Moreover, primary ovarian cancer cells have been shown to overexpress the ATP-binding cassette (ABC) sub-family G member (ABCG) 2 drug transporter protein, CXCR4 and CD133, and have been shown to have CSCs properties, including chemoresistance and tumor development [39].…”
Section: Heterogeneity Of Tumor Cells Before Treatmentmentioning
confidence: 99%